Analisa Yuridis Tentang Cacat Hukum Penetapan Ganti Kerugian Pengadaan Tanah Bagi Pembangunan untuk Kepentingan Umum dalam Pembangunan (Studi Putusan Mahkamah Agung Nomor 1382 PK/Pdt/2022) - Fika Amaly Putri Rais; Hasim Purba; Aflah (CV Rewang Rencang, 2025)
Land acquisition for infrastructure development in Indonesia as a developing country often leads to disputes regarding compensation determination, as in the case of Bener Dam in Purworejo Regency decided through Supreme Court Decision Number 1382 PK/Pdt/2022. This normative legal research with a descriptive-analytical approach examines compensation mechanisms based on legislation, the validity of deliberations in determining compensation, and legal considerations in dispute resolution. The results indicate that legal defects in compensation determination can occur due to non-communicative deliberation procedures, non-compliance with Law No. 2 of 2012, or violations of time limits. The Supreme Court rejected the judicial review application because the applicants failed to file objections to the District Court within 14 days as required by the applicable Supreme Court Regulations.